Structural style and growth of early-stage inversion structures: insights from 3D seismic reflection data, Egersund Basin, offshore Norway - Jackson,CAL; Chua,S-T; Bell,RE; Magee,C (Journal of Structural Geology, 2013)
High-quality three-dimensional (3D) seismic reflection and borehole data from the Egersund Basin, offshore Norway are used to characterise the structural style and determine the timing of growth of inversion-related anticlines adjacent to a segmented normal fault system. Two thick-skinned normal faults, which offset Permian clastics and evaporites, delineate the north-eastern margin of the basin. These faults strike NNW-SSE, have up to 1900 m of displacement and are separated by an ESE-dipping, c. 10 km wide relay ramp. Both of these faults display exclusively normal separation at all structural levels and tip out upwards into the upper part of the Lower Cretaceous succession. At relatively shallow structural levels in the hangingwalls of these faults, a series of open, low-amplitude, fault-parallel anticlines are developed. These anticlines, which are asymmetric and verge towards the footwalls of the adjacent faults, are interpreted to have formed in response to mild inversion of the Egersund Basin. The amplitude of and apparent shortening associated with the anticlines vary along strike, and these variations mimic the along-strike variations in throw observed on the adjacent fault segments. We suggest that this relationship can be explained by along-strike changes in the propensity of the normal faults to reactivate during shortening; wider damage zones and lower angles of internal friction, coupled with higher pore fluids pressures at the fault centre, mean that reactivation is easier at this location than at the fault tips or in the undeformed country rock. Seismic-stratigraphic analysis of growth strata indicate that the folds initiated in the latest Turonian-to-earliest Coniacian (c. 88.6 Ma) and Santonian (c. 82.6 Ma); the control on this c. 6 Myr diachroneity in the initiation of fold growth is not clear, but it may be related to strain partitioning during the early stages of shortening. Anticline growth ceased in the Maastrichtian and the inversion event is